Biological characterisation of HER2 amplified breast cancer - Barros, Fabrício Félix Tabuada (2013)
Breast carcinoma is the most frequent type of cancer affecting women. Among the recently described molecular and phenotypic classes of breast cancer, human epidermal growth factor receptor 2 (HER2)-positive tumours are associated with a poor prognosis. HER2 status is currently assessed in routine breast cancer reporting using immunohistochemistry (IHC) in addition to in situ hybridisation (ISH) in borderline cases. The ability of HER2 gene status to predict response to targeted therapy (Trastuzumab) is well documented. However, prognostic information provided by IHC expression categories and prognostic value added by using ISH in borderline cases remains unclear. HER2 plays an important role in cancer progression being targeted to provide predictive and prognostic information. Moreover, HER2 is related to cancer resistance against a variety of therapies; however, trastuzumab has proved successful in treatment of this subgroup. Nevertheless, patients may acquire resistance to this drug after a period of treatment, which indicates that other molecular mechanisms might influence success of this therapy. Dimerisation between members of the HER family may contribute to resistance against treatments due to different combinations that trigger different downstream pathways. This is promoted by ligands, which are expressed as transmembrane precursor protein molecules and have a conserved epidermal growth factor-like domain. Through resistance to trastuzumab, other drugs are being developed to interact in different domains of HER2 protein. The study of interaction between receptors/ligands will characterise specifically their signalling pathway and understand which strategy to acquire.